Advanced Mud Logging Based Spectral Gamma Ray Evaluation - Citra Wahyuningrum (Journal of Engineering Environtmental Energy and Science, 2026)
Real-time information on subsurface characteristics is crucial in oil and gas drilling activities to reduce risks and improve operational efficiency. One widely used method is logging, including the Spectral Gamma Ray (SGR) technique, which functions to identify formation types and natural radioactive content. The integration of SGR in Mud Logging allows for more accurate formation monitoring during drilling. The development of Advanced Mud Logging (AML) further strengthens this capability through Cutting analysis, thus producing more comprehensive Petrophysical Information Logs (PILs) as a basis for well evaluation. This study analyzes the application of SGR technology in the AML system in drilling Well C in Field W, with a focus on improving the accuracy and efficiency of subsurface formation characterization. Research data were obtained from gamma radiation measurements on Cutting and further analysis using X-Ray Fluorescence (XRF) and X-Ray Diffraction (XRD). Primary data comes from field measurements and laboratory analysis, while secondary data is obtained from related literature. The results show that SGR is able to provide real-time formation mapping with higher accuracy than conventional methods, while reducing ambiguity in lithology and stratigraphy interpretation. Comparison with Measurement While Drilling (MWD) data demonstrated a high degree of agreement, supporting the validity of this technology. Overall, this research contributes to the development of more efficient, responsive, and accurate drilling monitoring systems